Latvia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
Developments and prospects of nonbank financial institutions of Latvia have been presented in this paper. Foreign direct investment (FDI) inflows to Latvia have declined compared with their earlier levels. This poses an important policy challenge owing to benefits of FDI in terms of financing the current account deficit, contributing to capital formation, productivity, and exports. This paper also discusses the role of the Latvian Privatization Agency (LPA) in the privatization of Latvia's public enterprises and property, along with statistical data on economic indices of Latvia.